Molecule-based nonlinear optical switch with highly tunable on-off temperature using a dual solid solution approach - Shi-Yong Zhang (Nature Portfolio, 2020)
Switching of nonlinear optical signals is attractive for photoelectronics and photonics, but development is hindered by a lack of control over the switch temperature. Here the authors report a coordination polymer system that serves as an alloy-like nonlinear optical switch with a tunable switch temperature.